Understanding the Role of Multinational Enterprise Representatives in Indonesia Towards Geothermal Investment Opportunity in Emerging Economies - Arfian Rachmat Putra (Department of International Relations Universitas Pertamina, 2020)
Indonesia is a nation that is surrounded by aquatic resources and other major natural resources which can be utilize and converted to power through an investment program that allows investors to set up a clean energy project from hydro (river or reservoirs), wind, biomass, wave (ocean) and geothermal. The most significant issue which will be elaborated throughout this paper shall concentrate on the implication of internalization towards multinational enterprises by using existing geothermal energy development projects in Indonesia as study case. Indonesia’s natural resources has attracted foreign enterprises to invest in a state with emerging economies understanding that is still under development. Presently, Indonesia is still developing its regulation and availability to supply power demands from multiple areas that are rural, lack of electricity and lack of transmission lines. By comprehending the role of multinational enterprise which was triggered by the theory of internalization and investment.,